Age of male circumcision and risk of prevalent HIV infection in rural Uganda - Kelly, Robert; Kiwanuka, Noah; Wawer, Maria J.; Serwadda, David; Sewankambo, Nelson; Wabwire-Mangen, Fred; Li, Chuanjun; Konde-Lule, Joseph K.; Lutalo, Tom; Makumbi, Fred; Gray, Ronald H. (Aids, 1999)
Epidemiological evidence suggests that male circumcision may reduce the risk of sexually transmitted diseases (STD) and possibly HIV infection. Studies of STD clinic attenders have found that circumcised men are less likely to have gonorrhea, syphilis, herpes, candidiasis, and genital ulcer disease (GUD) [1–3]. Age at circumcision has also been reported as a risk factor in penile cancer [4]. Ecological studies report geographic correlations between HIV seroprevalence and the proportion of uncircumcised men in African populations [5,6], but subsequent cross-sectional and prospective studies found an inconsistent association between male circumcision and HIV-1 and HIV-2 infection in men and women [7–9].
Keywords: Male circumcision; HIV-1; sexually transmitted disease; Uganda; Africa